2011
DOI: 10.1111/j.1528-1167.2011.03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic increase in excitability in area CA1 after Schaffer collateral transection in vivo

Abstract: SUMMARY Purpose Epilepsy is a significant long-term consequence of traumatic brain injury (TBI) and is likely to result from multiple mechanisms. One feature that is common to many forms of TBI is denervation. We asked whether chronic partial denervation in vivo would lead to a homeostatic increase in the excitability of a denervated cell population. Methods To answer this question, we took advantage of the unique anatomy of the hippocampus where the input to the CA1 neurons, the Schaffer collaterals, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
5
16
1
Order By: Relevance
“…We have previously shown that this procedure results in very low amounts of cell death (Dinocourt et al 2011). We have also reported that SC transection results in a delayed and persistent increase in the excitability of the denervated CA1 cell population (Dinocourt et al 2011). We now report that this injury also triggers a delayed increase in the excitability of the CA3 cell population, as observed in ex vivo hippocampal slices from lesioned animals.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…We have previously shown that this procedure results in very low amounts of cell death (Dinocourt et al 2011). We have also reported that SC transection results in a delayed and persistent increase in the excitability of the denervated CA1 cell population (Dinocourt et al 2011). We now report that this injury also triggers a delayed increase in the excitability of the CA3 cell population, as observed in ex vivo hippocampal slices from lesioned animals.…”
Section: Discussionsupporting
confidence: 59%
“…To study the consequences of a relatively selective injury to the axons of brain cells in isolation, we developed a surgical approach to transect the SC pathway and thereby damage the axons of large numbers of CA3 pyramidal cells (Dinocourt et al 2011). We have previously shown that this procedure results in very low amounts of cell death (Dinocourt et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations